Keletas baltų ir slavų kalbų "semti" reikšmės veiksmažodžių ir jų kilmė - Karaliūnas, Simas (Baltistica, 1990)
SOME BALTIC AND SLAVIC VERBS DENOTING “DRAW, SCOOP” AND THEIR ORIGIN Some evidence (cf. Lith. griẽbti, griẽti, kabìnti, kaũšti, kõpti, Lith. kriẽti : Latv. krìet, Pr. kniēipe : Lith. kniẽpti, kneĩpti) indicates that the meaning “draw, scoop” is historically connected with the meaning “take, grasp, pick up”, on the one hand, and with the meaning “fasten, tack, clasp, press together, link, bind”, on the other. On this basis it is assumed that the etymological counterpart of Sl. *čъrрǫ, *čerpti “draw, scoop” is most likely Lith. kér̃pti (-ia) “bind, tie up”; Latv. smel̂t (smeļu, smêlu) “draw, scoop” belongs probably to the root *mel- “bind, tie, link” (with the “movable” s-), contained in Latv. sa-mel̂t (-meļu, -mêlu) “tie together, couple”, Tokh. AB mälk-, A malk- “join”, Hit. malk-, malkii̯a- “turn, twist together, spin” (<IE *mel-k-), and related lexemes of Lith. sémti (-ia, sė́mė) “draw, scoop” seem to be Lith. somúoti (-úoja, -ãvo) “to form a new strophe with another word when singing”, Tokh. sām- “take for oneself, conserve, preserve, amass”, A sum-, В sāmp- “take away, remove, lift, draw up”, Old Norse semja “put together, arrange, settle, adjust, order”, etc.